Trombay Phule Mustard 1: a yellow seed coat mutant of Brassica juncea with probable pleiotropic effect released as high yielding variety (Journal of Oilseed Brassica, 2026)
A yellow seed coat mutant Trombay Mustard 1 (TM1) of Indian mustard (Brassica juncea L) was isolated from parent variety Rai 5 using 32P radioisotope. Single plant selection from advance generations of TM1 has resulted into the isolation of high yielding variety TPM1. It was evaluated in national and state agricultural university yield trials. Average seed yield of TPM1 over 17 locations was 1396 kg/ha and oil yield was 631 kg/ha which is 21, 23, and 23 percent higher for seed yield and 37, 31, and 48% higher for oil yield over check varieties Sita, Pusa Bold and Varuna respectively. Therefore, it was released and notified by government of India for non-traditional area of mustard cultivation. Besides yellow seed coat, additional mutated characters are early, reduced plant height, high oil content, reduced erucic acid, powdery mildew and club root tolerance, heat tolerance and higher accumulation of arsenate. Direct mutant with many mutated characters has not yet reported so far. It could be probable pleiotropic effect of same mutated gene which is being reported first time.